The complete chloroplast genome of Horsfieldia hainanensis, an Endangered species with extremely small populations. Issue 2 (3rd July 2019) - Yang, Yong; Liu, Qiang; Chen, Yu-Kai; Wang, Yong; Chen, Qing
Abstract: Horsfieldia hainanensis is an Endangered species with extremely small populations, inhabiting the dense forest in ravines. It has high development and utilization value in the seed oil, fatty acids, volatile oils, and liposoluble constituent. In this study, the complete chloroplast genome of Horsfieldia hainanensis was sequenced. It is 155, 774 bp in size with a typical quadripartite structure: a large single-copy (LSC) region of 87, 124 bp, a small single-copy (SSC) region of 20, 612 bp, and 2 inverted repeat (IR) regions of 24, 020 bp. The genome contains 117 genes, including 75 protein-coding genes, 34 tRNA genes, and 8 rRNA genes, 13 genes have one intron and 3 three genes have two introns. The overall GC contents of the chloroplast genome was 39.1%. The phylogenetic tree based 11 complete chloroplast genome sequences of Magnoliales shows that H. hainanensis is closely related to Horsfieldia pandurifolia .